2001
DOI: 10.1007/s004210000365
|View full text |Cite
|
Sign up to set email alerts
|

Active recovery and post-exercise white blood cell count, free fatty acids, and hormones in endurance athletes

Abstract: Strenuous endurance exercise in fasted subjects is accompanied by increased plasma levels of catecholamines, leucocytosis, low insulin, and elevated plasma free fatty acids (FFA). Immediately after such exercise, plasma FFA may rise to high and potentially harmful levels, whereas the white blood cell count (WBCC) rapidly decreases towards or below baseline values. The present work investigated how active recovery (AR) for 15 min at 50% of maximal oxygen consumption (VO2max), after 60 min of uphill running at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
13
0
2
Order By: Relevance
“…In the presence of increased granulocyte and band cell counts, the constant counts of total circulating leukocytes after IRL were probably due to a fall in lymphocyte concentrations. This finding is consistent with previous findings after strenuous endurance exercise [21,22]. Physical exerciseinduced transient redistribution of peripheral blood is characterised by a granulocytosis accompanied by lymphocytosis during exercise, followed by a more pronounced granulocytosis accompanied by lymphopenia after exercise [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the presence of increased granulocyte and band cell counts, the constant counts of total circulating leukocytes after IRL were probably due to a fall in lymphocyte concentrations. This finding is consistent with previous findings after strenuous endurance exercise [21,22]. Physical exerciseinduced transient redistribution of peripheral blood is characterised by a granulocytosis accompanied by lymphocytosis during exercise, followed by a more pronounced granulocytosis accompanied by lymphopenia after exercise [22].…”
Section: Discussionsupporting
confidence: 93%
“…Physical exerciseinduced transient redistribution of peripheral blood is characterised by a granulocytosis accompanied by lymphocytosis during exercise, followed by a more pronounced granulocytosis accompanied by lymphopenia after exercise [22]. WIGERNAES et al [21] reported a continuous increase in neutrophils during active recovery with a fall in lymphocytes, which kept the total leukocytes constant at 120 min following a 60-min bout of uphill running at 83% of maximal oxygen uptake. In the present study, mononuclear cell counts tended to decrease in the IRL group at 6 h post-IRL compared with baseline, but the decrease did not reach a significant level, which could be due to the small change and small sample.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings are consistent with the vast exercise immunology literature, we have advanced understanding in this area by studying the effect of recovery interventions on immune activation. In our study, total leukocyte counts during active (10 minutes of cycling at 46,47 and the current study is likely due to the nature of the exercise task. Our findings are consistent with those of Jansky et al, 16 however, who found that a single cold-water immersion (14°C for 1 hour) created a small but significant increase in monocytes and lymphocytes.…”
Section: Immune Markersmentioning
confidence: 75%
“…The major limitation of the available studies is the lack of insight into mechanisms behind potential performance benefits or detriments to the use In the 15-to 60-minute period following exercise, lymphocyte counts tend to drop below resting values. 27 Wigernaes et al 46,47 found that active recovery (15 minutes at 50% VO 2peak ), as opposed to rest, prevented the initial fall in lymphocyte count after strenuous endurance exercise. Other recovery interventions, such as cryotherapy, may also influence immune system activation.…”
mentioning
confidence: 99%
“…Free fatty acids in the blood are a key source of energy for low/moderate intensity exercise [17]. During exercise, the concentration of free fatty acids in the blood increases.…”
Section: Discussionmentioning
confidence: 99%